Cytologic status changes of the conjunctiva and tears qualitative composition in patients with «dry eye» syndrome after instillation of modern topical fluoroquinolones - N. G. Zavgorodnyaya; A. A. Brizhan (Zaporožskij Medicinskij Žurnal)
Aim. Use of the antibiotics for eye was approved as a rational method for reducing the risk of postoperative endophthalmitis. The aim of our investigation was to study the influence of the modern topical fluoroquinolones on the qualitative composition of tears and cytological status of the conjunctiva in patients with cataract and «dry eye» syndrome.